OM-85 BV in pediatric recurrent respiratory tract infections: a cost-utility analysis - Jefferson Antonio Buendía; Diana Guerrero Patiño; Erika Fernanda Lindarte (BMC Pulmonary Medicine, 2022)
Abstract Background Despite the growing evidence on efficacy, little is known regarding the cost-utility of Vaxom/Imocur (OM-85 BV) supplementation to decrease the probability of recurrent respiratory tract infections in OM-85 BV to reduce the incidence of recurrent respiratory tract infections in children. Methods A decision tree model was used to estimate the cost and quality-adjusted life-years (QALYs) of OM-85 BV in a patient aged 1–6 with a history of recurrent respiratory tract infections. Multiple sensitivity analyses were conducted to evaluate the robustness of the model. Cost-effectiveness was evaluated using the willingness-to-pay defined for Colombia of US$5180 per QALY. The time horizon defined was six months. Costs were estimated from a societal perspective. Results The expected annual cost per patient with OM-85 BV was US$843 and with placebo was US$1167. The QALYs per person estimated with OM-85 BV was 0.91 and with placebo was 0.89. Conclusion In conclusion, our study shows that OM-85 BV is a cost-effective strategy to reduce the incidence of recurrent respiratory tract infections in children. Our study provides evidence that should be used by decision-makers to improve clinical practice guidelines.